Macrobrachium rosenbergii nodavirus (MrNV)-CP-RNA-2 DNA vaccine confers protective immunity in giant freshwater prawn Macrobrachium rosenbergii against MrNV infection. Issue 86 (March 2019) - Citarasu, Thavasimuthu; Lelin, Chinnadurai; Thirumalaikumar, Eswaramoorthy; Michael Babu, Mariavincent; Vakharia, Vikram N.
Abstract: Macrobrachium rosenbergii Nodavirus ( Mr NV) causes white tail disease (WTD) in Giant freshwater prawn Macrobrachium rosenbergii which leads to immense economic losses in hatcheries and farms. In the present study, we cloned the capsid protein gene of Mr NV-CP-RNA-2 (1146 bp) into a DNA vaccine vector pVAX1 to form Mr NV-CP-RNA-2- pVAX1. The bacterial transformant, containing the Mr NV-CP gene, was coated on the fish diet pellets and fed to juvenile M. rosenbergii for 40 days. After the vaccine delivery, group of M. rosenbergii were challenged with virulent Mr NV on 20 and 40 th days post-vaccination (dpv) respectively and monitored for the survival. The non-vaccinated M. rosenbergii succumbed to death (100%) within 5 days, whereas the Mr NV-CP-RNA-2- pVAX1 treated groups had the survivals of 60 and 80% in 20 and 40 dpv respectively (P ≤ 0.001). To study the Mr NV infection level, double step PCR was performed at different dpv. The results revealed that in 20 dpv group, the infection was decreased to 65% and in 40 dpv group the infection decreased to 69% from control diet fed prawns (P < 0.001). Haematological parameters like coagulation time, total haemocyte count (THC) and oxyhaemocyanin levels were performed for the control and vaccinated prawns. The vaccination helped to decrease the time of coagulation, improved THC and oxyhaemocyanin levels at a significant level (p < 0.001) when compared to the non-vaccinated group. The immunological parameters like prophenol oxidase (ProPO), superoxide anion and intra-agar lysozyme activity were also performed and the results revealed that the level of proPO, superoxide anion and lysozyme activities were significantly (P ≤ 0.05) increased in 20 and 40 dpv groups respectively, when compared with the non-vaccinated groups. Based on the vaccination trials, the DNA vaccine construct Mr NV-CP-RNA-2-pVAX1 effectively improved the survival against Mr NV challenge, helped to decrease viral load and enhanced the immune system to protect the prawn from Mr NV infection. This vaccine construct is highly useful to protect the M. rosenbergii from Mr NV infection. Graphical abstract: Image 1 Highlights: Mr NV-CP-RNA-2- pVAX1 DNA vaccine was constructed. Mr NV-CP-RNA-2- pVAX1 DNA vaccine was delivered to Macrobrachium rosenbergii . Mr NV-CP-RNA-2- pVAX1 DNA vaccine treated Macrobrachium rosenbergii had improved survival after Mr NV challenge. Mr NV-CP-RNA-2- pVAX1 DNA vaccine treated M. rosenbergii had improved immunity and reduced viral load.